Synthesis and annealing of nanostructured TiO2 films by radio-frequency magnetron sputtering - Hasan, M.M.; Haseeb, A.S. Md. Abdul; Saidur, Rahman; Masjuki, Haji Hassan; Hamdi, M. (Asian Network for Scientific Information, 2009)
In this investigation, anatase TiO 2 thin films were deposited on glass substrates at room temperature by RF magnetron sputtering at an elevated sputtering pressure of 3 Pa. The TiO 2 films deposited at room temperature were annealed at different temperatures up to 873Â°K for 1 h. The TiO 2 films were characterized by X-Ray Diffraction (XRD), Field-Emission Scanning Electron Microscopy (FESEM). Atomic Force Microscopy (AFM) and UV-visible-NIR spectrophotometry. The XRD results reveal that the as-deposited film possess the anatase structure. Annealed TiO 2 films show an insignificant change in crystallinity except of the fact that there is a slight increase for the film annealed at 600Â°C. The crystallite size increases from 44.5 to 48 nm with the increase of the annealing temperature. As-grown TiO 2 film exhibits high visible transmittance with enhanced refractive index of 2.31 at a wavelength of 550 nm. The indirect optical band gaps of the as-deposited and annealed films have been estimated to be in the range of 3.39-3.42 eV. AFM observations reveal the compact and dense morphology of the as-deposited and annealed TiO 2 thin films.